Das questões enunciativas aos mundos representados na Menina e Moça - Santos, Aida (1990)
This article questions the authenticity which during this century has beenattributed to the whole text common to the fifteenth century versions of Ber-nadim Ribeiro's «Menina e Moça». The characteristics noted point to ahetrogeneous text.